Pictorial directory 2000 (AORD, 2000)
A directory of the clery of the Roman Catholic Church based in Manila, supplemented with pictures. It also has a statistical profile with details such as total number, age distribution, orgination, and pastoral assignments as well as an index to the clergy, arranged by surname.